1998
DOI: 10.1038/nm0598-588
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic failure and liver cell damage in acute Wilson's disease involve CD95 (APO-1 /Fas) Mediated apoptosis

Abstract: Wilson's disease can result in fulminant liver failure due to hepatic copper overload. The CD95 system mediates apoptosis and has been demonstrated to be involved in liver disease. In this study CD95 mediated apoptosis was investigated in patients with fulminant hepatic failure in the course of Wilson's disease and in an in vitro model of copper treated human hepatoma cells. In patients, hepatic expression of CD95 and CD95L mRNA and apoptosis were detected. Copper overload in vitro resulted in hepatocytic apop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
129
0
8

Year Published

1998
1998
2009
2009

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 257 publications
(143 citation statements)
references
References 33 publications
6
129
0
8
Order By: Relevance
“…24 In our study, a membrane-bound CD95L 38-kd protein was evident in woodchuck-cultured and primary hepatocytes, and in HepG2 cells. In addition, a 28-kd protein representing the soluble form of the ligand was seen in woodchuck WCM-260 hepatocytes and PBMC.…”
Section: Discussionsupporting
confidence: 52%
See 3 more Smart Citations
“…24 In our study, a membrane-bound CD95L 38-kd protein was evident in woodchuck-cultured and primary hepatocytes, and in HepG2 cells. In addition, a 28-kd protein representing the soluble form of the ligand was seen in woodchuck WCM-260 hepatocytes and PBMC.…”
Section: Discussionsupporting
confidence: 52%
“…Previous attempts to identify CD95L protein in normal hepatocytes were not successful; however, the ligand has been detected in hepatocytes in some liver disorders and during allograph rejection [21][22][23][24] and in HepG2 cells. 24 In our study, a membrane-bound CD95L 38-kd protein was evident in woodchuck-cultured and primary hepatocytes, and in HepG2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fas is constitutively expressed on the surface of many cell types, including activated T and B-lymphocytes (Akagi et al, 1998;Li et al, 1996;Miyawaki et al, 1992), neutrophils (Iwai et al, 1994), endothelial cells (Sata and Walsh, 1988), keratinocytes (Matsue et al, 1995), liver cells (Strand et al, 1998) as well as in tumour cells (Leithouser et al, 1993). It has been shown that Fas triggers apoptosis via the activation of the caspase cascade (Ashkenazi and Dixit, 1998).…”
Section: Introductionmentioning
confidence: 99%